PENGARUH TEKANAN WAKTU, TEKANAN KETAATAN, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL PERSONIL APARAT PENGENDALIAN INTERNAL PEMERINTAH TERHADAP PENDETEKSIAN FRAUD - Gusti Dian Prayogi; Erina Sudaryati (BAJ: Behavioral Accounting Journal, 2019)
This study aims to determine the influence of time pressure, pressure of obedience, emotional intelligence and spiritual intelligence of Government Internal Control Apparatus in the Detection of Fraud Occurrence at Auditee. This research method uses verifikatif with quantitative approach. Hypothesis testers use statistical test tool that is Structural Equation Model (SEM) based on variance or better known as Partial Least Square (PLS). Sources of data in this study are primary data sources obtained directly, by conducting research and questionnaires. The number of respondents in the region is 70 auditors. Sampling technique using probability sampling with sample random sampling, in determining the number of samples used slovin formula. The results of this study indicate that time pressure and spiritual intelligence variables have no effect on fraud detection. APIP has been able to perform efficiently over time that has been compiled although the time limitations are very tight and rigid. The aspect of religiosity should be measured by a wider aspect. The variables of obedience pressure and emotional intelligence affect the detection of fraud. Pressure from superiors and clients can affect the independence of APIP by making changes to the examination results and ignoring the accumulated evidence.